AN ANALYSIS ON STUDENTS’ WRITING SKILL OF NARRATIVE TEXT AT XI GRADE OF IPA 2 OF SMAN 1 SALO - Harlinda Suita; Masrul Masrul (Universitas Pahlawan Tuanku Tambusai, 2018)
The purpose of this research is to know the students’ skill of XI Grade IPA 2 of SMAN 1 SALO in writing narrative text. The sample of this research is the second grade students of SMAN 1 SALO. The class consists of 20 students, the researcher used total sampling technique to determine the sample research. The research is a descriptive qualitative research. The purpose of this research is to describe the students’ writing skill of narrative text. This research was done with some steps. The steps are collecting the data, analyzing the data, making conclusions, and reporting result. The result of the research showed that the students’ writing skill of narrative text at second grade of SMAN 1 SALO in Excellent Category was 0%, in Good Category was 0%, in Fairly Good Category was 30%, in Weak Category was 55%, and in Poor Category was 15%. So, it can be concluded that the students’ writing skill in narrative text at second grade of SMAN 1 SALO was weak.